Factors shaping responsiveness towards sexual gender-based violence during the COVID-19 Pandemic in Africa: A systematic review - Malizgani Paul Chavula; Tulani Francis L. Matenga; Hikabasa Halwiindi; Caroline Hamooya; Noah Sichula; Deborah L Jones; Joseph Mumba Zulu (Taylor & Francis Group, 2023)
Abstract:Background: Several studies have been conducted on effects of COVID-19 on health, social and economic situation. However, evidence on the African continet on the responsiveness to sexual gender-based violence during the COVID-19 pandemic has not been adequately documented. This paper systematically reviews evidence from the African context regarding how countries responded to sexual gender-based violence during the height of the COVID-19 pandemic.Results: Drivers shaping the occurrence of SGBV included social and political responsiveness. The forms of SGBV experienced during the COVID-19 pandemic included; sexual; social- economic; physical emotional and domestic violence. Factors affecting responsiveness towards SGBV includes; limited availability or accessibility to the justice system, challenges accessing health services, inadequate human resources, fear of contracting COVID-19, social and economic barriers, and breakdown of social networks. Strategies for enhancing responsiveness included; training support, status on referral and linkages systems, protection services such as shelters and safety services, helplines and hotlines/communication, and collaboration on SGBV response.Conclusion: There is need to strengthen broader systems responsiveness through collaboration by creating strategies that promote reduction of SGBV. These strategies should include; community engagement to shift social -cultural norms towards gender and sexuality, creating social development opportunities for empowering and enabling women and girls with self-help and reliant activities, leveraging on community health systems structures to detect, link and monitoring of SGBV cases as well as co-integration of traditional justice system into the mainstream.